2004
DOI: 10.1093/treephys/24.5.561
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal sensitivity to vapor pressure deficit and its relationship to hydraulic conductance in Pinus palustris

Abstract: We studied the response of stomatal conductance at leaf (gS) and canopy (GS) scales to increasing vapor pressure deficit (D) in mature Pinus palustris Mill. (longleaf pine) growing in a sandhill habitat in the coastal plain of the southeastern USA. Specifically, we determined if variation in the stomatal response to D was related to variation in hydraulic conductance along the soil-to-leaf pathway (KL) over the course of a growing season. Reductions in KL were associated with a severe growing season drought th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
72
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(85 citation statements)
references
References 47 publications
10
72
0
3
Order By: Relevance
“…A high variability in hydraulic traits among closely-related Submediterranean deciduous oaks has been recently reported in two studies carried out in the Iberian Peninsula [12,19] Finally, we also found a significant correlation between k L, s−l and independent measurements of maximum leaf-level g s in both species (Fig. 9) as observed elsewhere for pine [1] and some angiosperm species [33], but still unreported for oaks. A linear relationship between g s and k L, s−L has been suggested to be characteristic of isohydric species (regulate ψ l at a constant value), while a curvilinear relationship has been attributed to anisohydric species (intermediate between constant ψ l regulation and no ψ l regulation) [20].…”
Section: Stomatal Control and Xylem Embolism: Coordination Of Liquid-supporting
confidence: 88%
“…A high variability in hydraulic traits among closely-related Submediterranean deciduous oaks has been recently reported in two studies carried out in the Iberian Peninsula [12,19] Finally, we also found a significant correlation between k L, s−l and independent measurements of maximum leaf-level g s in both species (Fig. 9) as observed elsewhere for pine [1] and some angiosperm species [33], but still unreported for oaks. A linear relationship between g s and k L, s−L has been suggested to be characteristic of isohydric species (regulate ψ l at a constant value), while a curvilinear relationship has been attributed to anisohydric species (intermediate between constant ψ l regulation and no ψ l regulation) [20].…”
Section: Stomatal Control and Xylem Embolism: Coordination Of Liquid-supporting
confidence: 88%
“…The response of plant water use to precipitation and soil water conditions is associated with stomatal control. Stomatal closure was identified as the main mechanism to regulate transpiration, avoiding irreversible damage to plant hydraulic system (Addington et al, 2004). Under drought stress conditions, stomatal conductance decreased with decreasing hydraulic conductance along the soil-to-leaf pathway due to high vapor pressure deficit (Motzer et al, 2005), xylem cavitation (Eberbach and Burrows, 2006), or soil dryness (O'Grady et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The exact mechanism underlying stomatal reactions to D has not yet been identified (Buckley 2005). Nevertheless, a strong correlation between g s and D led to the assumption of a functional relationship (Grantz 1990;Aphalo & Jarvis 1991;Addington et al 2004). However, other hypotheses, such as direct reactions to sap flow rate (Mott & Parkhust 1991;Monteith 1995) or hydro-active local feedback (Buckley 2005), have also been proposed.…”
Section: Discussionmentioning
confidence: 99%